(untitled) (Third Sector Social Economic Review, 2025)
Objective: The concept of leadership, which has gained a very important place in the field of management, has begun to attract much more interest by people in recent years with the effect of the change and development experienced worldwide. Many leadership studies conducted to date explain the positive and constructive characteristics of leaders. However, toxic leaders who misuse their authority, power and influence against the members of the organization can cause great harm to the organization and its members. One of these damages is employee burnout and, consequently, an increase in employee turnover intentions. In this context, since toxic leadership is an important phenomenon for today’s businesses, the aim of this study is to determine the effect of toxic leadership perception on turnover intention and to determine whether burnout plays a mediating role in this effect. Method: The study was conducted with the participation of 374 white-collar employees working in the accounting and finance sector. The data were analyzed with SPSS program. Results: As a result of the study, it was determined that toxic leadership perception has a high level effect on turnover intention and burnout plays a partial mediating role in toxic leadership and turnover intention. The results of the study reveal that the perception of toxic leadership causes organization members to experience burnout by psychologically challenging them and that the burnout of organization members is reflected in their turnover intentions.